An Increasing Trend of Illicit Drug use Among Romanian University Students From 1999 to 2011 - Lotrean Lucia Maria; Santillan Edna Arillo; Thrasher James; Laza Valeria (Sciendo, 2016)
The present study investigates the evolution of illicit drug use among Romanian university students from 1999 to 2011.